A ironia nos textos publicitários: estratégias de leitura para turmas do ensino médio - Silva, Paula Cristina Gomes da (2015)
The present work aims to form students-readers able to read and understand texts that present ironic speech in its composition, by making these readers more autonomous and more proficient. The theme choice was given by observing that students during high school, show difficulties in the reading and comprehension of texts that bring the element of irony. Based on Brait’s linguistic perspective (2008) and Brandão’s (2012); Carvalho’s (2014); Orlandi’s (2009) and Solé’s (1998) studies, we try searched for understanding the ironic phenomenon, its presence in the speech of advertising texts, besides getting the reading strategies that would help in the understanding of the advertisements. The methodology used was “action-research”, whose process was separated in three different moments: class observation, intervention time and class observation again. The research was applied in two classes at the 1st grade of high school in a part-time school of the metropolitan region of Recife. Based on the observation of classes at different times, i.e. before and after the intervention, we concluded that texts presenting ironic speeches are hardly understood by students-readers, and that the use of reading strategies can help in the irony’s understanding. Thus, it is necessary that the Portuguese teacher seek the appropriate strategies to work with their students and apply them consistently, contributing to a critical and integral formation of students.